The Role of Gender and Ethnic Diversity on the Performance of Malaysian Private Companies - Brahmana, Rayenda Khresna; Mohd Waliuddin, Mohd Razali (De La Salle University, 2017)
This study examines the effect of gender diversity and board diversity on Malaysian firm performance. This study is different from other studies because instead of using publicly listed companies, it uses 3,735 private companies over 2009–2014. We find that gender has no significant effect on the firm performance but firm’s characteristics such as firm age, firm’s size, liquidity, and leverage have significant effects on the firm performance. Our research further indicates that ethnic diversity in the board of directors may give better performance to companies. This research implies two important findings for the policy makers. First, the encouragement of gender equality to private companies by policy maker may fail as it does not have any impact. Second, policy maker should not consider ethnic diversity in the board as part of policy because it may reduce the firm performance.